The Effect of Principal Leadership and Educational Personnel Performance on Quality of Education in Tebing Tinggi City, Indonesia - Nizar, M. Alang Khairun; Mardayanti, Imelda; Haratikka, Haya; Arfah, Yenni; Arseto, Dedy Dwi (International Journal of Business, Economics & Financial Studies, 2023)
Quality of education has now become necessary for improving the quality of life of people throughout the country. Improving the quality of education will be directly proportional to the quality and level of welfare of the community, meaning that education is one way to improve the welfare and life of the community. Therefore, related to the issue of education, it is demanded that the government or the state must be present at the front in realizing the ideals of the state and nation. This study uses quantitative analysis techniques through Multiple Linear Regression. The results showed that the Principal's Leadership and Educational Personnel Performance influenced the Quality Improvement of Graduates at MTs Bustanul'Ulum Guppi Tebing Tinggi City. The simultaneous (overall) effect of the Principal's Leadership and Education Personnel Performance variables on improving the quality of education is 73.00%. The magnitude of the value is strong. Partially, the Principal's Leadership Variables and the Performance of Education Personnel were tested in influencing the Quality Improvement of Graduates at MTs Bustanul'Ulum Guppi Tebing Tinggi City: The results of the Principal's Leadership study affect the Quality Improvement of Graduates by 43 percent and Educational Personnel Performance of 30 percent. Other influences that are not studied or evaluated affect the quality of public services by 27 percent.